Perceived fear of COVID-19 infection according to sex, age and occupational risk using the Brazilian version of the Fear of COVID-19 Scale - Andrade, Eric Francelino; Pereira, Luciano José; Oliveira, Ana Paula Luiz de; Orlando, Débora Ribeiro; Alves, Débora Almeida Galdino; Guilarducci, Janina de Sales; Castelo, Paula Midori (Taylor & Francis, 2022)
We investigated the fear of COVID-19 infection after proper translation and cultural adaptation of the “Fear of COVID-19 Scale” to the Brazilian Portuguese language. A sample of 1,743 Brazilian participants were included. The scale showed excellent psychometric characteristics. Women showed higher anxiety levels. Fear of COVID-19 scores were lower in males with occupational risk of contamination. On the other hand, women and younger individuals showed higher fear of COVID-19 infection scores. The Brazilian Fear of COVID-19 Scale proved to be a reliable tool with excellent psychometric properties for identifying fear of COVID-19 infection in the Brazilian population.